2016
DOI: 10.3389/fpls.2016.01037
|View full text |Cite
|
Sign up to set email alerts
|

Plant Recycling for Molecular Biofarming to Produce Recombinant Anti-Cancer mAb

Abstract: The expression and glycosylation patterns of anti-colorectal cancer therapeutic monoclonal antibody (mAb) CO17-1A recognizing the tumor-associated antigen GA733-2, expressed in human colorectal carcinoma cells, were observed in the leaf and stem tissues of primary (0 cycle), secondary (1 cycle), and tertiary (2 cycle) growths of seedlings obtained from the stem cut of T2 plants. The bottom portion of the stem of T2 seedlings was cut to induce the 1 cycle shoot growth, which was again cut to induce the 2 cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…The approach is completely flexible since the specific part of it could be easily re-designed for various targets. 194 Kim et al 195 targeting approaches for recombinant protein accumulation. [196][197][198] Importantly, in one study, in order to find the best extraction method for recombinant monoclonal antibodies from tobacco plants, various factors have been evaluated including pH, temperature, mechanical disruption method, buffer composition, etc.…”
Section: Production Of Recombinant Anti-cancer Monoclonal Antibodiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The approach is completely flexible since the specific part of it could be easily re-designed for various targets. 194 Kim et al 195 targeting approaches for recombinant protein accumulation. [196][197][198] Importantly, in one study, in order to find the best extraction method for recombinant monoclonal antibodies from tobacco plants, various factors have been evaluated including pH, temperature, mechanical disruption method, buffer composition, etc.…”
Section: Production Of Recombinant Anti-cancer Monoclonal Antibodiesmentioning
confidence: 99%
“…Selection of the best plant species for steady alteration and management of environmental parameters which influence plant fitness conditions are very critical. 114,195,[207][208][209] In one study, Lim et al 210 demonstrated that colorectal cancer vaccine protein levels in stems and leaves reaped after flower fertilization were smaller than the plant material gathered before the blossoming period. As a result, the highest manifestation level of a colorectal cancer vaccine protein was reported in the 12 weeks after the in vitro plant seedlings were transplanted.…”
Section: Production Of Recombinant Anti-cancer Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations
“…We obtained homozygous seeds from transgenic Arabidopsis thaliana plants expressing anti-CRC mAb P s (mAb CO and mAb CO tagged with KDEL (mAb COK)) to recognize CRC-associated antigen GA733 (EpCAM), which is highly expressed in CRC cells [18, 19]. To confirm the effects of ER retention motif tagging on transgenic Arabidopsis , the KDEL motif was fused to the C-terminus of the original HC.…”
Section: Introductionmentioning
confidence: 99%